ZAKAH FOR WATER: AN ALTERNATIVE SOURCE OF FUNDING FOR SUSTAINABLE ACCESSIBILITY - Marga Gumelar (UNEJ e-Proceeding)
This paper aims to discuss an alternative instrument for water infrastructure financing to support universal access to safe water by the use of zakah funds. Taking a case in Aceh, a province in the western peak of Indonesia that adopted sharia law, this study simulated some financing models based on three basic assumptions i.e. pessimistic scenario, moderate scenario, and optimistic scenario. The need for financing is laid on the operations expenditures of municipal water utilities (MWUs), as the prime providers of water service, and the source of funding is the realization of zakah collection, both of which include the total number of municipalities and cities in the province. The study resulted, even in the pessimistic scenario, that the use of zakah funds is able to increase the number of population served twice. This article recommends the integration of implementation of the existing zakah programs for water infrastructure into a single project with a focus on a particular area to have a fundamental impact on the community.